APLIKASI METODE ANALYTICAL HIERARCHY PROCESS (AHP) DALAM PEMILIHAN KONTRAKTOR DI PT. DSS SERANG - Budiharjo Budiharjo (Universitas Mercu Buana, 2014)
Abstract. PT. DSS is engaged in the generation of electrical energy trying toimprove their quality to ensure the availability and reliability of electricity andsteam distribution to customers. Then the company has always tried to maintainthe operational continuity of power generation engines. One way to implementimprovements boiler and turbine overhaul alternately and must be completed on-time schedule, it must be done by a competent contractor. To ensure thecompetence of the contractor to overhaul the necessary research to evaluate itsperformance aimed at selecting the best contractor. From the research results withAnalytical Hierarchy Process (AHP) methode is known that most prioritizedcriteria in the selection of contractors is a priority quality criteria with a weight of0.539, other criteria is the cost (0.297) and the criteria for cooperation (0.164).The best contractors being the top priority is PT. NWI with the largest priorityvalue is 0.276, then PT. CMS (0.248), PT. TJ (0.175), and PT. KDS (0.173).Contractors whose value is the lowest priority are PT. CAS for 0.067 and PT. DE(0.052).Keywords: Overhaul, Analytical Hierarchy Process (AHP), Criteria, Matrix,Priority